Discussion on the duration of response following HBsAg clearance in patients with chronic hepatitis B treated with PegIFNα-2b - Wang, Tao; Tang, Fei; Li, Fenghui; Chen, Jing; Yan, Fei; Du, Qin; Yin, Weili; Liang, Jing; Liu, Lei; Wang, Fang; Xu, Baiguo; Ye, Qing; et al. (Frontiers in Immunology, 2025)
AimFunctional cure strategies based on interferon therapy for chronic hepatitis B (CHB) are gaining increasing attention among clinicians. However, studies investigating the duration of response after achieving HBsAg clearance with interferon treatment are limited. This study aims to explore the patterns of sustained response following HBsAg clearance in patients treated with pegylated interferon alpha-2b (PegIFNα-2b) through long-term follow-up, providing guidance for clinical practice.MethodsWe collected data from CHB patients who achieved HBsAg clearance and were treated with either PegIFNα-2b monotherapy or in combination with nucleos(t)ide analogs (NAs) at Tianjin Third Central Hospital from January 2018 to May 2024. Regular follow-up assessments were conducted to observe the dynamic changes in HBsAg, HBV DNA, and liver function during the follow-up period. We recorded the time to HBsAg reversion (defined as HBsAg ≥ 0.05 IU/mL), analyzed the patterns of HBsAg reversion, and investigated the optimal time points for evaluating sustained HBsAg clearance.ResultsA total of 173 patients with CHB or compensated hepatitis B cirrhosis were included. The mean age was 41.5 ± 9.0 years, with 16.19% of patients having compensated cirrhosis. The median follow-up duration was 89.3 weeks (range: 18.6 to 289.1 weeks). HBsAg reversion occurred in 26 patients, yielding a reversion rate of 15.03% (26/173). Among these 26 patients, 50% (13/26) experienced reversion within 24 weeks, and 80.77% within 48 weeks; thereafter, the number of reversions gradually decreased. At 48 weeks post-treatment cessation, the HBsAg sustained response rate was 95.45%, stabilizing at 100% after 120 weeks. Among patients with regular follow-ups, virtually none experienced reversion beyond 72 weeks. At the time of HBsAg reversion, all 26 patients exhibited normal alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total bilirubin (TBIL) levels, with a median HBsAg level of 0.70 IU/mL (range: 0.05 to 8.13 IU/mL), and only one patient showing low-level positive HBV DNA (117 IU/mL). No adverse events, including liver failure, decompensation, or hepatocellular carcinoma, occurred during the follow-up period.ConclusionsPatients with chronic hepatitis B treated with PegIFNα-2b demonstrated favorable long-term persistence of HBsAg clearance. However, there remains a risk of HBsAg reversion after treatment cessation, predominantly within the first 48 weeks. HBsAg sustained response (HSR) at 48 weeks post-treatment is a critical follow-up time point for CHB patients post-HBsAg clearance, with HSR at 72 weeks potentially representing an ideal follow-up timeframe, while HSR at 120 weeks may serve as a marker for extended follow-up.